Atención al cliente en la Ferretería Ferreconst de la parroquia san juan del Cantón San Francisco de Puebloviejo en el periodo 2022 - Avilés Zooller, Brillith Katiuska (2023)
The "Ferreconst" hardware store is an organization dedicated to the commercialization of construction materials and other hardware items, it is located in the San Juan Parish of the Cantón San Francisco de Puebloviejo, as any entity has the purpose of maximizing its profits through the increase of sales, but at the same time its objective is focused on providing a quality service to the client to satisfy their needs through the products offered, therefore, to generate an environment of satisfaction between the seller and the buyer, the objective is to diagnose customer service at the Ferreconst hardware store in the San Juan parish of the San Francisco de Puebloviejo canton in the period 2022, which is achieved through the analytical and field method; methodology that allowed to analyze and know the current situation of the company in relation to customer service, but the correlation of variables contributed to conclude that there are difficulties around the attention provided to the user, being able to conclude that policies and processes related to the customer satisfaction, for which the generation of a work plan for the training of employees in the customer service area is recommended, whose positive evolution allows improving sales levels.